Study on the Tooth Surface Equation and Parametric Modeling for New Type of Cylindrical Gear with Arc Tooth Trace - Li Qin; Liu Haidong; Zhang Qi (Jixie chuandong)
The cylindrical gear with arc tooth trace is a novel cylindrical gear with the features of good meshing performance,large overlap coefficient,smooth transmission,low noise,high efficiency,long service life and so forth. It can make up the deficiency of the existing gear transmission pairs. In order to further study its characteristic,the tooth surface equation is deduced according to the processing principle of rotationary cutter for the cylindrical gear with arc tooth trace and meshing principle. Also,in order to improve the modeling efficiency,the parametric three- dimensional modeling of the rotating disk method is completed based on the secondary development technology. This provides the correct 3D model for the following simulation analysis.